A rare cause of familial exogenous Cushing syndrome - Rajan, Remya (J Family Med Prim Care, 2019)
Exogenous steroid use is the most common cause of Cushing syndrome. With the use of glucocorticoids(GC) for a variety of diseases, the indiscriminate use of this group of drugs has increased. We present a family from which both children were brought with features suggestive of Cushing syndrome. On evaluation, they were found to have suppressed hypothalamic pituitary adrenal (HPA) axis, signifying steroid use from exogenous sources. On further evaluation by a psychiatrist, the mother who was on treatment for chronic depression confessed that she had bought dexamethasone tablets over the counter, and administered the same, mixed with fruit juices to her sons. The family was counselled regarding the consequences of chronic steroid abuse and the children were started on replacement doses of prednisolone. Certain features like posterior subcapsular cataract, glaucoma, avascular necrosis of femur and psychosis are specific to exogenous Cushing syndrome. Despite efforts to understand the effects of long-term steroid treatment on the HPA axis, it is not yet clear as to which patients will have prolonged HPA axis suppression. The time taken for the recovery of HPA axis remains variable. Also, HPA axis suppression due to exogenous steroids may present as acute adrenal crisis. Hence, it is important to start these patients on replacement dose of steroids and also educate them regarding the increased requirement of steroids during stress.